Woolworth strike, 1962 (1962)
1962 1960-2000 "Woolworth strike, 1962" [EP0032], 1962 This poster was produced by the Union of Shop, Distributive and Allied Workers in support of the strike for union recognition and representation at Woolworth. The poster shows women on a picket line outside the store.